Implications Position Auction Minutes in State Administrative Law regarding Legal Studies in Higher - Br. Turnip, Lydia Fransiscani (Universitas Pahlawan Tuanku Tambusai, 2025)
Understanding jurisdictional boundaries between law administration and civil law becomes aspect important in education law. This study analyzes position treatise auction in law state administration and the implications of learning law in college high. The method used is qualitative descriptive with a normative approach, focused on the analysis of regulation legislation, including Constitution Number 5 of 1986 concerning State Administrative Court and Regulation implementation auction, as well as relevant literature in civil and administrative law. Research results show that treatise auctions are more appropriately categorized in civil law because they document administrative transaction auctions without decision ties in a way law administration does. Uncertainty jurisdiction between Justice Civil and PTUN confirmed the need for a comprehensive approach to learning law. Implications study. This covers strengthening understanding of normative, studying case treatise auction in the eye, studying law state administration, and integrating interdisciplinary approaches. Thus, students can develop an analysis critical to the system of justice and understand the complexity of jurisdiction law in Indonesia.